The Problem of Adaptation of Students in Higher Educational Institutions and II Levels of Accreditation to Work Inpositions in Primary Health Care Settings - Grishnjaeva, E. (Psychiatry, Neurology and Medical Psychology, 2016)
The current stage of the operation and the reorganization of the health system in Ukraine requires training of medical professionals who are able to quickly adapt to the working conditions in health-care facilities, which vary as a result of difficult socio-economic conditions in the country. The specialists of the new generation should be able to deal effectively with increasingly complex and diverse professional tasks. Modern hospitals need graduates who can use the theoretical knowledge and practical skills to improve them; be able to introduce innovative approaches in practice and training.